STUDY OF THE STUDENTS’ OPINION ON THE ORGANIZATION AND HOLDING OF UNIVERSITY WINTER GAMES AND WINTER UNIVERSITY - D. Elinova (Trakia Journal of Sciences)
The purpose of university sports is to create conditions and inspiration for all students around the world to practice sports. The organization and holding of university games, especially winter games, creates a favorable environment for active dialogue between the student communities in universities in Bulgaria, through their participation in trainings, seminars, sports and cultural events. The purpose of the present study is to examine the opinion of the participants in the University Winter Games and Winter University and, on this basis, to find a way to maximally satisfy the interests and needs of the participants. A survey method was used for the purpose of the study. The survey card contained 29 questions, of which only a part of the questions related to the objectives of the study were used. The subject of the study were 26 participants, of whom 10 were women and 16 were men. The obtained results were analyzed and presented based on the analysis of percentages (%).